Level of Knowledge on Sexual and Reproductive Health Among Youths in Southern Region of Peninsular Malaysia - Ja’afar, Siti Mariam; Awang, Hafizuddin; Rahman, Azriani Ab (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: Premarital sexual activity is associated with low level of knowledge of sexual and reproductive health which gives less control over decision making pertaining to sexuality. Low understanding of sexual and reproductive health knowledge made adolescents unaware of the consequences of premarital sexual activity. This study aimed to describe the knowledge of sexual and reproductive health among youths in the state of Johor, in southern region of peninsular Malaysia. Materials and Methods: A crosssectional study was conducted in eleven health facilities in Johor state, Malaysia. The study samples were all youths who fulfilled study inclusion and exclusion criteria. The youths were assessed through a validated self-administered, anonymous questionnaire on sociodemographic background and 21 items of knowledge on sexual and reproductive health. Descriptive statistics were employed to present the findings. Results: There were 204 respondents involved in the study. The mean (±standard deviation) age of respondents was 21 years old (±1.9). Majority of them were female (60.7%) and Malay (89.1%). Most of the respondents had high level of education (secondary and tertiary levels) (98.5%). A small percentage of the respondents were smokers (18.6%), alcohol drinkers (7.5%), drug users (3.5%), and a smaller portion reported of having history of sexually molested (4%). This study found sexual exposure among subjects ranged from reading (35.3%) and watching pornographic materials (44%), imagining sex (18.2%), as well as masturbating (21.1%). As for level of knowledge on sexual and reproductive health, majority of our respondents had low level of knowledge on the domain of sexual activity and pregnancy, complication of premarital sexual activity, and contraception. Conclusion: As the involvement of youths in sexual activity is getting more prevalent, youth sexual and reproductive health should be prioritized in Malaysia. Public health campaigns need to focus on the positive aspects of healthy sexual relationships. The importance of ensuring easy access to sexual and reproductive health services for all youths needs to be acknowledged and addressed. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 315-323